Op weg na ’n opvoedkundige etiek: problematiek rondom die terme etiek. sede en moraal - Roux, P. J. le (Koers, 1992)
One of the initial problems which not only ethics as an emerging science has to cope with, but also special sciences like education which have to employ ethical perspectives, is the lack of a unanimous scientific interpretation of the concepts ethics, mores and morals. A direct consequence of this state of affairs is that ethicists differ widely in respect of their views regarding the field of investigation of ethics as a science. What it really amounts to is that different ‘ethicists' are largely operating in dissimilar scientific fields. It stands to reason (hat it is hard to conduct a meaningful scientific discourse about ethical matters in this way and that the results of a great deal of research in ethics will be extremely confusing - not only to ethicists, but, amongst others, to educationists, parents, students and pupils as well, especially with regard to present day problems in respect of sexual relationships, drug abuse, protest art, political turmoil in educational (and other) matters, etc. In this article an account is given of some currcnt interpretations of the concepts ethics, mores and morals and an attempt is made at indicating possibilities which can be explored in the quest for solutions to this dilemma.